1985
DOI: 10.1029/jc090ic03p04883
|View full text |Cite
|
Sign up to set email alerts
|

Drifter trajectories through a current meter array at Drake Passage

Abstract: Six low‐profile undrogued buoys drifted through the Drake Passage during 1979 where an extensive array of current meters was moored. Geostrophic currents at the buoy positions are estimated by extrapolating the shallow 40‐hour low‐pass filtered current measurements to the surface by using vertical shear relationships derived from hydrographie stations taken over a 5‐year period within the passage. The buoy tracks are also filtered, followed by the removal of the extrapolated geostrophic currents. The residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
2
5
0
Order By: Relevance
“…In a study of drifter trajectories through a current meter array at Drake Passage, Peterson [ 1985] Figure 11: (a) potential temperature, (b) salinity, (c) potential density, (d) oxygen, (e) nitrate, (f) phosphate, (g) silicate, and (h) water mass summary. Hydrographic stations are indicated by triangles along the top of each panel, and XBT stations are shown by dots above Figure 12a.…”
Section: Drifter Trajectories In the Abcs Study Areasupporting
confidence: 70%
“…In a study of drifter trajectories through a current meter array at Drake Passage, Peterson [ 1985] Figure 11: (a) potential temperature, (b) salinity, (c) potential density, (d) oxygen, (e) nitrate, (f) phosphate, (g) silicate, and (h) water mass summary. Hydrographic stations are indicated by triangles along the top of each panel, and XBT stations are shown by dots above Figure 12a.…”
Section: Drifter Trajectories In the Abcs Study Areasupporting
confidence: 70%
“…The difference in drift speed between drogued and undrogued buoys as well as the correlation between drift and wind speed could be verified. Undrogued buoys drifted with about 2.5% of the wind speed, a figure that agrees well with the 3.4 -+ 1.4% given by Peterson [1985]. Furthermore, it was found that drifter acceleration as well as the variance of the mean drift speed are also larger for undrogued buoys.…”
Section: General Differences In Drift Behaviorsupporting
confidence: 84%
“…A potentially useful tool for high-latitude studies is the coastal zone color scanner (CZCS). Peterson [1985] demonstrated that there is a high degree of correlation between surface drifter trajectories and near-surface flow observed in CZCS imagery. Satellite altimetry also may prove useful for tracking features in the ACC.…”
Section: Discussionmentioning
confidence: 88%